Law and justice in Japanese popular culture from crime fighting robots to duelling pocket monsters - Pearson, Ashley; Giddens, Thomas; Tranter, Kieran (Routledge, 2018)
Cover -- Title -- Copyright -- Contents -- List of illustrations -- Preface -- List of contributors -- 1 Crime fighting robots and duelling pocket monsters: Law and Justice in Japanese Popular Culture -- Part I Possibilities of justice -- 2 The symptoms of the just: PsychoPass, judg(e)ment, and the asymptomatic commons -- 3 Pirates, giants and the state: legal authority in manga and anime -- 4 Traumatic origins in Hart and Ringu -- 5 Justice in the sea of corruption: Nausicaä as ecological jurisprudence -- 6 Masterful trainers and villainous liberators: law and justice in Pokémon Black and White -- Part II The legal subject -- 7 Doing right in the world with 100,000 horsepower: Osamu Tezuka's Tetsuwan Atomu (Astro Boy), essence, posthumanity and technohumanism -- 8 Caught in couture: regulating clothing and the body in Kill la Kill -- 9 'Holy transjurisdictional representations of justice, Batman!': globalisation, persona and mask in Kuwata's Batmanga and Morrison's Batman, Incorporated -- Part III The power and problem of the image -- 10 'Finding the law' through creating and consuming gay manga in Japan: from heteronormativity to queer activism -- 11 Regulating counterpublics in yaoi online fan communities -- 12 'Is yaoi illegal?!': let's get real about the potential criminalisation of yaoi -- 13 Constitutional analysis of secondary works in Japan: from otaku to the world -- Part IV Specificities of law and justice in everyday Japan -- 14 'The world is rotten': execution and power in Death Note and the Japanese capital punishment system -- 15 Debts, family, and identity after the collapse of the bubble: Miyabe Miyuki's All She Was Worth -- 16 Rules and unruliness in manga depictions of community police boxes -- 17 The imagecharacters of criminal justice in Tokyo -- Index
Keywords: Justice in mass media; Law in mass media; Mass media -- Social aspects -- Japan; Comic books, strips, etc -- Social aspects -- Japan; Animated films -- Japan -- History and criticism; Popular culture -- Japan; Aufsatzsammlung